Effects of sensory integration training on balance function and executive function in children with autism spectrum disorder: evidence from Footscan and fNIRS - Deng, Junchen; Lei, Ting; Du, Xiru (Frontiers in Psychology, 2023)
Introduction This study investigates the efficacy of sensory integration training (SIT) in enhancing balance and executive functions in children with autism spectrum disorder (ASD), with the aim of highlighting its potential for organizing and processing sensory information in the brain. Methods Utilizing Footscan for biomechanical evidence and functional near-infrared spectroscopy (fNIRS) for neural activation, we engaged two participant groups: a control group (n = 9) and an experimental group (n = 9). Assessments involved the Sharpened Romberg Test (SRT) for balance under varied visual conditions and the Go/No-Go task for executive function. Results The SIT intervention significantly improved balance function, particularly in Visual Deprivation (VD) scenarios. Neurophysiological data revealed heightened activation in the right Inferior Frontal Gyrus (R-IFG) and right Middle Frontal Gyrus (R-MFG), suggesting enhanced executive function. The potential of R-IFG/MFG activation as a reliable biomarker for assessing executive function in ASD was identified. Discussion The study provides empirical evidence supporting SIT’s effectiveness in enhancing balance and executive functions in children with ASD. The therapy not only improves sensory processing and motor skills but also appears to compensate for sensory deficits, particularly in vision, vestibular perception, and proprioception. Enhanced neural activation in specific PFC regions underscores SIT’s role in improving cognitive aspects, including inhibitory control and cognitive flexibility. The multidisciplinary approach adopted for this research highlights the intricate interplay between sensory-motor functions and cognitive control in ASD, paving the way for integrated therapeutic strategies. Despite these advancements, the mechanisms through which SIT exerts these multifaceted effects require further exploration.